UPAYA IRAN UNTUK MEMPERTAHANKAN PROGRAM NUKLIR DI TENGAH TEKANAN AMERIKA SERIKAT DI ERA PRESIDEN HASSAN ROWHANI TAHUN 2014 - Subchan Asmarahadi (HI 15 UMY 403, 2015)
*403 The title of this research is "The efforts of Iran to Maintain Nuclear Program In Central Pressure United States in the Era of President Hassan Rowhani 2014". The nuclear program of Iran in the era of President Ahmad Dinejat always rejected negotiations with western countries or tend confrontational, but changes the political dynamics inside Iran with the election of Iranian President Hasan Rowhani as Iran's president opened up opportunities for Western countries, especially the United States to suppress the Iranian president Hasan Rowhani to resolve problems related to Iran's nuclear program. In analyzing the typology used theory Theory of Foreign Policy and Diplomacy. Methods of data collection through library research (library research). The data collected will be processed qualitatively and using deductive method. The success of Iran to maintain its nuclear program is influenced by judging strategy on US foreign policy that is considered likely to be "threatening" and an assessment of the ability of Iran itself does not feel "weaker" or "stronger"; which then resulted in a policy of "defensive". Besides Iran also used the conference diplomacy as a means to prove to the US and around the world that Iran's nuclear program is solely for peaceful purposes. Multilateral diplomacy efforts made in the era of Iranian President Hassan Rohani more moderate. In an effort to maintain its nuclear program amid opposition to the West, Iran through diplomacy or official channels trying to achieve its national interests to comply with international rules official and legitimate. Government and the Iranian people never backward in defending their rights in the civil nuclear field in accordance with international treaties, the Charter of the International Atomic Energy Agency (IAEA), as well as the principle of national sovereignty of Iran itself. Open and official diplomacy conducted by Iran make protective legality of the development of the nuclear program in the country. Keyword: Nuclear Program, Pressure, Diplomacy